Management control system in asnaf entrepreneurship development program by Lembaga Zakat Selangor - Nor Hayati Samba Mohamed,; Nor’Azam Mastuki,; Sharifah Norzehan Syed Yusuf,; Maheran Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Lembaga Zakat Selangor (LZS) has been corporatized and governed as a corporate entity. For good corporate governance, LZS implements a management control system (MCS) in one of its zakat distribution program known as Asnaf Entrepreneurship Development Program (AEDP). The objective of study is to explain the elements/dimensions of MCS in AEDP by referring to Levers of Control (LOC) as a framework. The LOC with four control mechanisms namely belief, boundary, interactive and diagnostic is commonly known, preferable and applied framework for MCS research and adopted by many worldwide corporations. A total of eight interviews were carried out; three with LZS officers and five with zakat beneficiaries. Data were audio recorded, transcribed verbatim and analysed in qualitative approach. It was found that the controls available in LZS can be matched against four control mechanisms in LOC. Despite that all the four control mechanisms are placed in MCS, they have yet to be documented in LZS Standard Operating Procedure (SOP). Formal documentation may impetus confidence amongst zakat payers and Muslims as a whole that the funds are efficiently managed and properly governed for the best interest of beneficiaries apart from being source of references to other zakat institutions.